2021
DOI: 10.1136/bmj.n1837
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual property waiver for covid-19 vaccines will advance global health equity

Abstract: and colleagues argue that a temporary intellectual property waiver for covid-19 vaccines is vital to increase supply, achieve global herd immunity, and advance global health equity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 5 publications
0
23
0
7
Order By: Relevance
“…This was achieved with the AIDS crisis, but only after many years and many more deaths. Poorer countries require relaxation of intellectual property rights, technology transfer, and support to rapidly establish regional vaccine manufacturing hubs 31. Africa, Asia, and Latin America are perfectly capable of producing vaccines, and to claim otherwise is a misleading argument 31…”
Section: Knowledge Must Be Sharedmentioning
confidence: 99%
“…This was achieved with the AIDS crisis, but only after many years and many more deaths. Poorer countries require relaxation of intellectual property rights, technology transfer, and support to rapidly establish regional vaccine manufacturing hubs 31. Africa, Asia, and Latin America are perfectly capable of producing vaccines, and to claim otherwise is a misleading argument 31…”
Section: Knowledge Must Be Sharedmentioning
confidence: 99%
“…Over time, people without access to resources such as strong health systems, health workers, medicines, and vaccines have become the majority of those who develop Covid-19 infections and die. One publication reported that by late June 2021, 46% of people in high income countries had received at least one dose of Covid-19 vaccine compared with 20% in middle income countries and only 0.9% in low income countries (2). Equitable vaccine distribution was clearly not happening.…”
Section: Working To Achieve Access To High Quality Medicines and Rati...mentioning
confidence: 99%
“…The 1995 Trade Related Aspects of Intellectual Property Rights (TRIPS) Agreement was set up to provide minimum protection standards for intellectual property, which included pharmaceutical products and vaccines (4). South Africa and India submitted a proposal to the World Trade Organization (WTO), in October 2020, to allow licensing of Covid-19 health products and technologies under the TRIPS agreement (2). They and other countries would then be able to produce Covid-19 medical goods locally and effectively import or export them.…”
Section: Working To Achieve Access To High Quality Medicines and Rati...mentioning
confidence: 99%
See 1 more Smart Citation
“…A waiver can also facilitate creation of future manufacturing hubs, engaging a greater number of manufacturers, and ultimately yield more doses faster ( Erfani et al 2021 ). It can “prevent companies that hold the IP for COVID-19 vaccines from blocking vaccine production elsewhere on the grounds of IP and allow countries to produce COVID-19 medical goods locally and import or export them expeditiously” ( Erfani et al 2021 , 2). Ultimately, it can “help drive down the cost of vaccines, therapeutics, and diagnostic tools, and result in increased access in the developing world” ( Zarocostas 2021 , 1871).…”
Section: Introductionmentioning
confidence: 99%